Enseñanza-aprendizaje de la multiplicación a través del juego simbólico - Fonseca Rico, Gina Katherine (Universidad Antonio Nariño, 2023)
In the first years of school there are several difficulties that children encounter as they advance in the subjects. One of the most obvious is learning multiplication, since the step from adding and subtracting to multiplying involves a procedural change that can affect student performance, which can lead to a lack of motivation and disinterest in mathematics.